2017
DOI: 10.3389/fnhum.2017.00387
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Gaze Strategies for Locomotion with Constricted Visual Field

Abstract: In retinitis pigmentosa (RP), loss of peripheral visual field accounts for most difficulties encountered in visuo-motor coordination during locomotion. The purpose of this study was to accurately assess the impact of peripheral visual field loss on gaze strategies during locomotion, and identify compensatory mechanisms. Nine RP subjects presenting a central visual field limited to 10–25° in diameter, and nine healthy subjects were asked to walk in one of three directions—straight ahead to a visual target, left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 82 publications
0
20
0
Order By: Relevance
“…While the rest of visual field allows for an appropriate spatial orientation and navigation, its low spatial resolution impairs drastically object, face recognition and reading (Safran et al 1999 ; Boucart et al 2010 ). Reversely, peripheral visual field loss excludes the use of covert visual attention, constraining the affected individuals to increase their saccade rate to laboriously explore their environment (Authié et al 2017 ). Affected individuals preserve functions related to the high spatial resolution of the residual central vision such as face and small objects recognition but exhibit impaired spatial orientation (Wittich et al 2011 ) and scene perception (Fortenbaugh et al 2007 ), altered postural control (Berencsi et al 2005 ) and increased risk of object collision during locomotion (Turano et al 1999 , 2002 ) due to the limited coverage of the residual visual field.…”
Section: Introductionmentioning
confidence: 99%
“…While the rest of visual field allows for an appropriate spatial orientation and navigation, its low spatial resolution impairs drastically object, face recognition and reading (Safran et al 1999 ; Boucart et al 2010 ). Reversely, peripheral visual field loss excludes the use of covert visual attention, constraining the affected individuals to increase their saccade rate to laboriously explore their environment (Authié et al 2017 ). Affected individuals preserve functions related to the high spatial resolution of the residual central vision such as face and small objects recognition but exhibit impaired spatial orientation (Wittich et al 2011 ) and scene perception (Fortenbaugh et al 2007 ), altered postural control (Berencsi et al 2005 ) and increased risk of object collision during locomotion (Turano et al 1999 , 2002 ) due to the limited coverage of the residual visual field.…”
Section: Introductionmentioning
confidence: 99%
“…We evaluated which types of mobility situations cause the greatest self-perceived anxiety for people with dry AMD. Our methods were novel and offer an important advantage over methods of assessing mobility directly in the real world or in a built life-like environment, such as the Pedestrian Accessibility and Movement Environment Laboratory at University College London, UK, 18 and the Streetlab artificial street, Paris, France, 19 in that they may be conducted in a safe environment, free from health and safety risks. The test may be presented in different ways, including through virtual/ augmented reality platforms, and on portable electronic devices.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear to what extent results from the present study's highly synthetic tasks with limited field of view are generalizable to real-word conditions, but laboratory-based COMR has been shown to correlate well with ''outdoor COMR'' measured during passive viewing in a naturalistic setting. 24 In the only study to our knowledge that has commented on both eye and head movement in PVFL, Authié et al 7 showed that during locomotion, head position was more variable in RP than in controls, but eye position variability was similar. This result is congruent with our results, showing an increased propensity for head movement in RP.…”
Section: Limitationsmentioning
confidence: 99%
“…6 In the only PVFL study to our knowledge that has considered the relative contributions of eye and head movement, participants with RP used increased horizontal head movement and a similar eye movement during locomotion compared with healthy sighted controls. 7 None of the aforementioned studies have considered age or field of view extent as possible correlates for eye and head behavior in RP. It is known that healthy subjects can adapt to artificial restrictions of the field of view or oculomotor range by increasing the relative contribution of head movement to overall gaze movement, but it remains unclear whether this effect is observed in RP.…”
mentioning
confidence: 99%